Spatial Absorbency Assessment for Sustainable Land Development - Broża, Noemi; Birnbaum, Karolina; Garcia Castro, David; Kazak, Jan K. (Geomatics and Environmental Engineering, 2020)
Sustainable land use development requires a smart decision‑making process based on appropriate spatial design patterns. However, the pro‑investment policy of many municipalities often results in disproportions between the de‑mand and supply of investment areas, which means that spatial development is not realized in a sustainable way. In order to avoid the overconsumption of land for investment purposes, central government in Poland introduced a requirement to assess land balance, which includes the calculation of spa‑tial absorbency at the level of local urban planning. The aim of this work is to develop the concept of spatial absorbency assessment. In order to select best practices, document reviews of local spatial policies in Kalisz, Łódź, Toruń and Gdańsk were performed. Based on the review, a method for spatial absorbency assessment was presented. The applicability of the proposed solution is pre‑sented by its use on the case of the Racibórz municipality. The visualization shows what kind of geoinformation is required to perform an assessment by means of the developed method. The results of the calculations present the final feedback that is received by local authorities. The work was carried out us‑ing ArcGIS software. The obtained results may constitute the basis for further multi‑dimensional analyses as part of sustainable land development planning at the local level.